Long non coding RNA biology - Rao, M. R. S. (Springer, 2020)
This contributed volume offers a comprehensive and detailed overview of the various aspects of long non-coding RNAs and discusses their emerging significance. Written by leading experts in the field, it motivates young researchers around the globe, and offers graduate and postgraduate students fascinating insights into genes and their regulation in eukaryotes and higher organisms.